Urbanicity and Mental Health in Europe: A Systematic Review - Kohler, Stefan; Penkalla, Anna Maria (European Journal of Mental Health, 2014)
Urbanicity has been described as a risk factor for mental disorders. Findings differ across countries and psychiatric outcomes. Our aim was to systematically review quantitative studies of the relationship between urbanicity and prevalent mental disorders in Europe. EBSCOhost and PubMed databases were searched for epidemiological studies of European populations, published in English between January 2002 and October 2012, using the combination of keywords (urban* OR environment*) AND (mental health OR mental disorder OR psych*). The eleven studies included in the review used studies used different measures of urbanicity. The types of mental disorders most often examined, on which we focus in the review, were mood and anxiety disorders, psychosis, and substance use disorders. Urbanicity was associated with mental health. Seven out of nine studies reported more mood and anxiety disorders in some of the urban areas compared to rural areas. Two out of three studies indicated higher rates of psychosis in some more urbanised areas. Four out of six studies found more substance abuse with increased urbanicity. The same studies neither found any evidence for a relationship between urbanicity and mental disorders in several instances. Living in an urban environment in Europe can be a risk factor for mood and anxiety disorders, psychotic disorders, and substance abuse. More research is needed to understand which urban environment characteristics cause mental disorders.